Finding the right dose: a scoping review examining facilitation as an implementation strategy for evidence-based stroke care - Oyebola Fasugba; Heilok Cheng; Simeon Dale; Kelly Coughlan; Elizabeth McInnes; Dominique A. Cadilhac; Ngai W. Cheung; Kelvin Hill; Kirsty Page; Estela Sanjuan Menendez; Emily Neal; Vivien Pollnow; et al. (Implementation Science)
Abstract Background Despite evidence supporting interventions that improve outcomes for patients with stroke, their implementation remains suboptimal. Facilitation can support implementation of research into clinical practice by helping people develop the strategies to implement change. However, variability in the amount (dose) and type of facilitation activities/facilitator roles that make up the facilitation strategies (content), may affect the effectiveness of facilitation. This review aimed to determine if, and how, facilitation dose is measured or reported and the type of facilitation strategies used to support adoption of stroke interventions in hospitals and subacute settings. We also assessed whether the included studies had reporting checklists or guidelines. Methods The scoping review was based on Arksey and O’Malley’s framework. Cochrane, CINAHL and MEDLINE databases were searched to identify randomised trials and quasi-experimental studies of stroke interventions published between January 2017 and July 2023. Accompanying publications (quantitative, qualitative, mixed methods or process evaluation papers) from eligible studies were also included. Narrative data synthesis was undertaken. Results Ten studies (23 papers) from 649 full-text papers met the inclusion criteria. Only two studies reported the total facilitation dose, measured as the frequency and duration of facilitation encounters. Authors of the remaining eight studies reported only the frequency and/or duration of varying facilitation activities but not the total dose. The facilitation activities included remote external facilitator support via ongoing telecommunication (phone calls, emails, teleconferences), continuous engagement from on-site internal facilitators, face-to-face workshops and/or education sessions from external or internal facilitators. Facilitator roles were broad: site-specific briefing, action planning and/or goal setting; identifying enablers and barriers to change; coaching, training, education or feedback; and network support. Only two studies included reporting checklists/guidelines to support researchers to describe interventions and implementation studies in sufficient detail to enable replication. Conclusions There is a paucity of information on the measurement of facilitation dose and reporting on specific details of facilitation activities in stroke implementation studies. Detailed reporting of dose and content is needed to improve the scientific basis of facilitation as strategic support to enable improvements to stroke care. Development of a standardised measurement approach for facilitation dose would inform future research and translation of findings.